Corpora and Translation. Are Corpora Still an Academic Luxury? - Grigaliūnienė, Jonė (Vertimo studijos, 2019)
This paper aims to consider the impact corpora have made on language studies and to touch upon the interface between corpora use and translator training/practice. A small-scale survey conducted among the translation trainers/professionals and translation students, with the aim of finding out whether professional translators and students are aware of the existence of corpora and to what extent they use them in their work, revealed that both the trainers and the students are well aware of corpora, but they still prefer translation memory technology to using corpora when translating. They have also pointed out that they would be interested in a service which quickly provided domain-and-language specific corpora tailored to their needs and a tool for extracting terminology from a domain specific corpus. The paper presents a tool which is now widely available for academic institutions in Europe and which gives a chance to quickly and easily compile a specific corpus, extract keywords, provides concordances and gives a useful word sketch that could be of great help when translating. The paper concludes that corpora have yet to make an impact on translation studies and that this will depend on raising awareness of the usefulness of corpora for translation training and practice and the availability of corpora tools that could meet translator needs.